EFFECT OF DIAZINON ON SOME BLOOD PARAMETERS IN MALE RABBITS - A.AL.Quim , M. (The Iraqi Journal of Veterinary Medicine, 1996)
This study was designed to investigate the acute toxic effect of Diazinon on some blood parameters. Twelve male rabbits were divided randomly and equally into two groups, A treated group (T) and control group (C). Animals of group (T) were dipped in 3:1000 diazinon solution. Within 24 hours following the treatment, animals of group (T) showed moderate symptom of organophosphorous poisoning such as dyspnia and depression. Blood analysis of the group (T) animals revealed a significant elevation of blood sugar and urea. These changes were correlated with increased W.B.C. counts. The results of this study indicate that dipping with diazinon is not free of side effects on certain physiological functions of body systems.